Radiolabelling of peptides with tetrazine ligation based on the inverse electron-demand Diels-Alder reaction: rapid, catalyst-free and mild conversion of 1,4-dihydropyridazines to pyridazines - Otaru Sofia; Martinmäki Tatu; Kuurne Iida; Paulus Andreas; Helariutta Kerttuli; Sarparanta Mirkka; Airaksinen Anu J. (ROYAL SOC CHEMISTRY, 2025)
Click chemistry reactions, such as the tetrazine ligation, based on the inverse-electron demand Diels-Alder (IEDDA), are chemoselective cycloaddition reactions widely used for chemical modifications and synthesis of biomolecule-based radiopharmaceuticals for positron emission tomography (PET). The reactions have potential also for pretargeted PET imaging. When used as a bioconjugation method in production of biomolecule-based radiopharmaceuticals, IEDDA-based tetrazine ligation has one significant drawback, namely the formation of a mixture comprising reduced metastable dihydropyridazines (DHPs) and oxidized cycloadducts. Conversion of the reduced DHPs to stable pyridazines requires oxidation, which is typically achieved by using oxidants or by photo-irradiated air-oxidation, both methods requiring added reagents or reaction times of several hours, not compatible with short-lived radionuclides. Here we report a mild, rapid, and catalyst-free conversion of the DHPs to pyridazines. In this study, a model peptide Tyr3-octreotide (TOC) was modified with polyethylene glycol (PEG) linkers and with trans-cyclooctenes (TCOs) for rapid IEDDA-mediated radiolabeling. Fluorine-18-labelled alkylammoniomethyltrifluoroborate ([18F]AmBF3) tetrazines were conjugated to the TCO-TOC analogs at room temperature for rapid synthesis of PET imaging agent candidates. The formed DHPs were successfully converted to the oxidized form, after heating the radiolabelled bioconjugates in aqueous solution (≥95% water) at 60 °C for a minimum of 10 minutes in the presence of air, resulting in one-pot back-to-back IEDDA reaction and DHP conversion. The water content of the reaction mixture was to be found critical for the coversion. Our finding offers a straightforward method for conversion of the metastable DHPs from the IEDDA-based tetrazine ligation to stable, oxidized pyridazines. The method is especially suitable for applications requiring rapid conversion.